2019
DOI: 10.1021/jacs.8b12929
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Au/Ag Dual-Catalyzed Cross-Dehydrogenative Biaryl Coupling: Reaction Development and Mechanistic Insight

Abstract: An operationally simple and highly selective Au/Ag bimetallic-catalyzed cross-dehydrogenative biaryl coupling between pyrazoles and fluoroarenes has been developed. With this reaction, a wide range of biheteroaryl products can be obtained in moderate to good yields with excellent functional group compatibility. The exact role of silver salts, previously overlooked in most gold-catalyzed transformations, has been carefully investigated in this biaryl coupling. Insightful experimental and theoretical studies ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 72 publications
(97 reference statements)
7
83
0
Order By: Relevance
“…Possible mechanisms for the heterocoupling of terminal alkynes and alkynyl hypervalent iodiner eagents triggered by Au-TA/AgOTs catalysts and phene ligands. [214] Similart ot he findings by Zhu et al, [102] the Ag I catalyst activatest he CÀHb ond of the cyclopropane, whereas the Au catalyst activates the alkyne coupling partner (Scheme 31). OxidativeAu-catalyzed1,2-difunctionalization of ethyleneand proposed mechanisms.…”
Section: Cooperative Au/m (M = Ag or Pd) Bimetallic Cross-coupling Resupporting
confidence: 80%
See 3 more Smart Citations
“…Possible mechanisms for the heterocoupling of terminal alkynes and alkynyl hypervalent iodiner eagents triggered by Au-TA/AgOTs catalysts and phene ligands. [214] Similart ot he findings by Zhu et al, [102] the Ag I catalyst activatest he CÀHb ond of the cyclopropane, whereas the Au catalyst activates the alkyne coupling partner (Scheme 31). OxidativeAu-catalyzed1,2-difunctionalization of ethyleneand proposed mechanisms.…”
Section: Cooperative Au/m (M = Ag or Pd) Bimetallic Cross-coupling Resupporting
confidence: 80%
“…During the synergistic homogeneousA u/Pd-catalyzed cross-coupling reactions, the Au complex acts initially as ac onventional pphilic Lewis acid catalyst and then undergoes af acile Au/Pd transmetalation. [102] DFT calculations and experimental studies indicated that Ag I activates the CÀHb ond of electron-poor arenes, whereas the Au III intermediate activates the CÀHb ond [200] of the electron-richa rene coupling partner. In 2015, Larrosa and co-workers developed Au I /Au III -catalyzed synthesis of unsymmetrical biarylst hrough a cross-dehydrogenative coupling assisted by Ag additives.…”
Section: Cooperative Au/m (M = Ag or Pd) Bimetallic Cross-coupling Rementioning
confidence: 97%
See 2 more Smart Citations
“…Zhu et al . designed an operationally simple and highly selective Au/Ag bimetallic‐catalyzed cross‐dehydrogenative biaryl coupling between pyrazoles 140 and fluoroarenes 141 (Scheme ) . From the theoretical calculations they proposed that silver acetate is the actual catalyst for C−H activation of electron‐poor arenes, rather than the previously reported gold(I)‐catalyzed process.…”
Section: Gold‐catalyzed Csp2−h Bond Activation Processesmentioning
confidence: 99%